Association of Lymphatic Abnormalities with Early Complications after Fontan Operation - Dittrich, Sven; Weise, Anja; Cesnjevar, Robert; Rompel, Oliver; Rüffer, André; Schöber, Martin; Moosmann, Julia; Glöckler, Martin (Thoracic and Cardiovascular Surgeon, 2021)
Background Increased central venous pressure is inherent in Fontan circulation but not strongly related to Fontan complication. Abnormalities of the lymphatic circulation may play a crucial role in early Fontan complications. Methods This was a retrospective, single-center study of patients undergoing Fontan operation from 2008 to 2015. The primary outcome was significant early Fontan complication defined as secondary in-hospital treatment due to peripheral edema, ascites, pleural effusions, protein-losing enteropathy, or plastic bronchitis. All patients received T2-weighted magnetic resonance images to assess abdominal and thoracic lymphatic perfusion pattern 6 months after Fontan completion with respect to localization, distribution, and extension of lymphatic perfusion pattern (type 1-4) and with application of an area score (0-12 points). Results Nine out of 42 patients developed early Fontan complication. Patients with complication had longer chest tube drainage (mean 28 [interquartile range [IQR]: 13-60] vs. 13 [IQR: 2-22] days, p = 0.01) and more often obstructions in the Fontan circuit 6 months after surgery (56 vs. 15%, p = 0.02). Twelve patients showed little or no abnormalities of lymphatic perfusion (lymphatic perfusion pattern type 1). Most frequently magnetic resonance imaging showed lymphatic congestion in the supraclavicular region (24/42 patients). Paramesenteric lymphatic congestion was observed in eight patients. Patients with early Fontan complications presented with higher lymphatic area score (6 [min-max: 2-10] vs. 2 [min-max: 0-8]), p = 0.001) and greater distribution and extension of thoracic lymphatic congestion (type 3-4: n = 5/9 vs. n = 1/33, p = 0.001). Conclusion Early Fontan complication is related to hemodynamic factors such as circuit obstruction and to the occurrence and extent of lymphatic congestion.
CRIS-Team Scopus Importer:2021-01-15
Keywords: cardiovascular magnetic resonance imaging; congenital heart disease; Fontan operation; lymphatic perfusion pattern